Comprehensive management application of sulodexide on proteinuria: 2 case reports - Li Zhou; Wenge Li (Frontiers in Medicine)
Proteinuria is an important sign of kidney function decline and one of the common clinical manifestations in patients with chronic kidney disease and diabetic kidney disease, which are often accompanied by a gradual decline in kidney function. Therefore, effective management of proteinuria is of great significance for delaying the progression of kidney disease and protecting kidney function. Sulodexide is a mixture of fast-moving heparin and dermatan sulfate with anticoagulant, thrombolytic, anticardiovascular, lipid-lowering, and renal-protective effects. It has potential application value in the comprehensive management of proteinuria. This study reported two different chronic disease cases to explore the comprehensive management application of sulodexide in patients with long-term poor proteinuria control. Case 1 is a 45 years-old male with type 2 diabetes mellitus and hypertension accompanied by persistent proteinuria and intermittent edema in both legs. Case 2 is a 52 years-old female with chronic nephritis and rheumatoid arthritis accompanied by persistent proteinuria and edema in both legs. Two patients showed a decrease in urinary protein levels and stable control of the remaining signs of disease after the addition of sulodexide to their comprehensive treatment regimens, indicating that sulodexide plays an important role in the comprehensive management of proteinuria.